A history of violence: testing the 'culture of honor' in the US South - Pauline Grosjean (Fondazione Eni Enrico Mattei (FEEM), 2010)
Using historical data on early settlers to the United States, this paper tests and confirms the 'Culture of Honor' hypothesis by socio-psychologists Dov Cohen and Richard Nisbett (1994, 1996). This hypothesis argues that the high prevalence of homicides in the US South stems from the fact that it was a frontier region settled by people whose economy was based on herding: the Scotch-Irish. Herding societies develop cultures of honors for reasons having to do with their precariousness: violence is a necessary condition to preserve a reputation for toughness and deter animal theft. Using historical census data on waves of settlers from Europe and relating contemporaneous violence to early Scotch-Irish settlers, this paper provides a test of the link between Scotch-Irish settlers and the culture of honor. The results confirm that high numbers of Scotch-Irish immigrants to the US South by 1790 are associated with higher homicide rates today, including homicides by white offenders. Similar results do not hold for different origins of migrants or other violent crime or offenses. The effect is stronger in counties with high headcounts of pigs and sheep in the 19th century, confirming the herding origin of the culture of honor. An important contribution of this paper is to suggests an instrument for violence, based on past economic occupations and ecological suitability for herding vs. farming.
Keywords: K4; Z; Z13; 330; Cuture of honor; US South